Risk factors for mortality in critically ill infants with acute kidney injury: A resource‐limited setting experience. Issue 2 (2nd August 2021) - Mishra, Om P.; Verma, Avdhesh Kumar; Abhinay, Abhishek; Singh, Akanksha; Singh, Ankur; Prasad, Rajniti
ABSTRACT: Infants with acute kidney injury (AKI) who are critically ill often will have multiorgan dysfunctions. Objective of the present study was to find out mortality, recovery of kidney function at discharge and at 3 months, and to determine risk factors for mortality. Fifty‐two infants (24 newborns and 28 postneonatal) with AKI were included. Staging was done as per Kidney Disease Improving Global Outcomes classification. Patients were subjected to medical treatment and peritoneal dialysis (PD), wherever indicated. Kidney function tests were performed at admission, discharge, and at 3 months follow‐up. Median age of neonates was 8 days and postneonatal infants were 4.5 months. Stage 1, 2, and 3 AKI were present in 14 (26.9%), 16 (30.7%), and 22 (42.3%) cases, respectively. PD was required in 22 (42.3%) infants, and significantly higher in postneonatal than in neonates (57.1% vs. 25%, p  < 0.05). Significant recovery of kidney function occurred at discharge and cases had normal parameters at 3 months. Mortality was 17.3%. Patients had significantly higher risk of mortality, if they had metabolic acidosis (OR 13.22, CI 2.33–74.94, p  = 0.002) and needed ventilation (OR 14.93, 95% CI 1.7–130.97, p  = 0.006) and PD (OR 6.53, 95% CI 1.20–35.48, p  = 0.026). In logistic regression analysis, fluid overload ( p  < 001), hypotension ( p  < 0.01), and higher PRISM‐III score ( p  < 0.05) were found as significant risk factors for mortality. Medical management including PD led to good recovery of kidney function. Presence of fluid overload, hypotension, and higher PRISM‐III score adversely affected the outcome.